1998
DOI: 10.1080/10408699891274200
|View full text |Cite
|
Sign up to set email alerts
|

Butyric Acid from the Diet: Actions at the Level of Gene Expression

Abstract: A number of components present in the diet, although nutritionally nonessential, have been discovered to have beneficial effects toward both general health and disease prevention/protection. One such nutrient, butyric acid, can be derived in large quantities from bacterial fementation of dietary fiber in the bowel and is also a component of bovine milk. In gut fermentation, the production of butyric acid defines its delivery point; thus, the synthesis and site of action of butyric acid are in close proximity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(84 citation statements)
references
References 0 publications
2
80
0
2
Order By: Relevance
“…Experimental studies in vivo, and in colonocytes, colon carcinoma cell lines and inflammatory cells indicate that butyrate may exert protective anti-inflammatory and anticarcinogenic effects by several mechanisms (Smith et al, 1998;Luhrs et al, 2002;Menzel et al, 2004). Our own studies have shown that it was possible to increase the faecal butyrate level by giving patients with ulcerative colitis a diet supplemented with b-glucan enriched oat bran (Hallert et al, 2003).…”
Section: Introductionmentioning
confidence: 90%
“…Experimental studies in vivo, and in colonocytes, colon carcinoma cell lines and inflammatory cells indicate that butyrate may exert protective anti-inflammatory and anticarcinogenic effects by several mechanisms (Smith et al, 1998;Luhrs et al, 2002;Menzel et al, 2004). Our own studies have shown that it was possible to increase the faecal butyrate level by giving patients with ulcerative colitis a diet supplemented with b-glucan enriched oat bran (Hallert et al, 2003).…”
Section: Introductionmentioning
confidence: 90%
“…Hence, chemotherapeutic agents in combination that restore the normal apoptotic pathways have the potential for effectively reducing cancer risk (24,55). Although it has been well documented that butyrate is an inhibitor of histone deacetylases and can activate the Fas receptor-mediated extrinsic death pathway (23,60,66), the role of these mechanisms in the induction of colonocyte apoptosis may be a secondary consequence of its ability to promote cellular oxidation (40,42). For example, serving as the primary energy source for colonic epithelial cells, butyrate induces cellular ROS generation (8,42).…”
Section: Discussionmentioning
confidence: 99%
“…The central role of butyrate on colonocyte physiology suggests the necessity of an exquisite regulation of butyrate availability for both energy production and gene expression in these cells (1,2,34,62,65). Thus, we evaluated if the modifications of the gut ecosystem following HP diet ingestion are associated with metabolic changes toward butyrate (and other energy substrates) in isolated colonic epithelial cells or if, conversely, metabolic homeostasis is maintained in these cells after such a dietary modification.…”
mentioning
confidence: 99%